The Integration Transfer of Knowledge and Transfer of Value in The Book Ta’līm al-Muta’allim Written By Syaikh Az-Zarnuji - Muhamad Ridwan; Mustofa Aji Prayitno; M. Miftahul Ulum; Basuki Basuki (AL-ISHLAH: Jurnal Pendidikan, 2024)
Moral education is one of the most important parts of Islamic teachings. Islamic teachings oblige all adherents to seek knowledge, and one of the most prioritized knowledge is ilmu al-hāl. This study aims to reveal the concept of ethics in seeking knowledge and the integration between transfer of knowledge and the transfer of value based on the book of Ta’līm al-Muta’allim written by Syaikh Az-Zarnuji. This study uses qualitative research methods that focus on library research. Sources of data used include the book Ta’līm al-Muta'alim as a primary data source and related journal articles as a source of supporting data. The data analysis process uses the content analysis method, which includes: (1) Identifying and describing; (2) interpreting and analyze; (3) drawing conclusions. The results showed that Syaikh Az-Zarnuji in his book Ta’līm al-Muta’allim emphasized that education is not only a place to increase intellectual knowledge and skills, but the most important thing in the educational process is the value transfer process in order to improve the morals and behavior of students. This is reflected in the concepts of education in the book Ta’līm al-Muta’allim whose contents do not only discuss education as a means of knowledge transfer (transfer of knowledge), but also emphasizes the educational process as a transfer of moral values and goodness (transfer of values).